Habitat Suitability Modeling of Javan Rhino (Rhinoceros sondaicus Desmarest 1822) Ujung Kulon National Park - U Mamat Rahmat; Yanto Santosa; Lilik Budi Prasetyo; Agus Priyono Kartono (Jurnal Manajemen Hutan Tropika, 2012)
Javan rhino (Rhinoceros sondaicus Desmarest 1822) is the rarest species among 5 species of rhinos in the world. Its distribution is currently limited only in Ujung Kulon National Park (UKNP), Indonesia. Due to the small population size and its limited distribution, it is listed as critically endangered species in the IUCN Redlist. The main objectives of this research were: 1) to identify the dominant habitat components that determine the presence of javan rhino in UKNP; 2) to analyze habitat suitability of javan rhino (Rhinoceros sondaicus Desmarest 1822) in UKNP using geographical information system; and 3) to examine its habitat condition. Results of the research found eight components identified to be crucial for Javan rhino habitat and appropriate for spatial modelling of habitat suitability, of which four were the most dominant factors influencing the frequency of javan rhino presence. These four dominants factors were slope, distance from wallow sites, distance from rumpang (open area), and distance from beach.